2016
DOI: 10.1021/acs.jpcc.6b10106
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity and Reactivity of Pd-Rich PdGa Surfaces toward Selective Hydrogenation of Acetylene: Interplay of Surface Roughness and Ensemble Effect

Abstract: Recent experiments have shown that PdGa nanocrystallites act as highly selective and reactive catalyst for selective hydrogenation of acetylene to ethylene. Motivated by these experimental results we have studied the mechanism and energetics of the above reaction on low indexed (100) and (110) PdGa surfaces using first-principles density functional theory based calculations. We find that the energetically favorable (100) surface created by cleaving the crystal in the less dense region shows reasonably good sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…the H-Pd bond length in H2 adsorption structure was 1.83 Å , and the H-H bond length was also increased from 0.74 Å to 0.79 Å , the adsorption energy was −6.19 kcal/mol. For the S-doped N sites, the optimal adsorption sites for the C2H2 and H2 molecules are at the top of the Pd atom, but the position of the Pd atom changes to the left N atom in the six-fold cavity, which is consistent with the results reported previously [13]. The C-C bond length in the C2H2 adsorption structure increases from 1.205 Å to 1.261 Å , the C-Pd bond length is 2.06 Å , the bond angle also changes from 180° to 155.5°, with the adsorption energy of −21.62 kcal/mol.…”
Section: Adsorption Of Reactantssupporting
confidence: 91%
See 1 more Smart Citation
“…the H-Pd bond length in H2 adsorption structure was 1.83 Å , and the H-H bond length was also increased from 0.74 Å to 0.79 Å , the adsorption energy was −6.19 kcal/mol. For the S-doped N sites, the optimal adsorption sites for the C2H2 and H2 molecules are at the top of the Pd atom, but the position of the Pd atom changes to the left N atom in the six-fold cavity, which is consistent with the results reported previously [13]. The C-C bond length in the C2H2 adsorption structure increases from 1.205 Å to 1.261 Å , the C-Pd bond length is 2.06 Å , the bond angle also changes from 180° to 155.5°, with the adsorption energy of −21.62 kcal/mol.…”
Section: Adsorption Of Reactantssupporting
confidence: 91%
“…In order to improve the performance of g-C 3 N 4 , recent studies have proposed the strategy that g-C 3 N 4 also can be used as an excellent substrate for supporting catalysts to anchor single metal atoms and catalyze various reactions due to its more specific N species and larger N coordination cavity [9][10][11]. In 2015, Vilé and colleagues [12] investigated and studied a stable single catalyst that could anchor Pd atoms in the cavities of g-C 3 N 4 while it could not anchor stably on Al 2 O 3 supports, and it seems that active site isolation reduces the formation of high hydrocarbons (green oils) and improves the selectivity of catalysts, as also demonstrated for other types of reactions [13][14][15]. Motivated by these observations, Gao et al [16] first studied the reduction of carbon dioxide by Pd/g-C 3 N 4 as photocatalyst through density functional theory, which showed that the photocatalysts exhibit excellent activity in CO 2 reduction.…”
Section: Introductionmentioning
confidence: 98%
“…This equation indicates that the more positive the Δ E a , the more selective the catalyst will be for the production of ethylene compared with ethane formation. As table 1 shows, B 11 N 12 Pd has a better selectivity than most bimetallic alloys [ 13 , 16 , 17 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results show that a Pd single atom can effectively dissociate an H 2 molecule, which is consistent with the demonstration of Sykes and co-workers [ 19 , 38 , 39 ]. From the selectivity formula, we conclude that the selectivity of the B 11 N 12 Pd SAC is higher than that of the majority of the bimetallic alloy single-atom catalysts [ 16 , 17 , 26 ]. Our work indicated that the B 11 N 12 Pd SAC might be a promising candidate for selective hydrogenation reactions.…”
Section: Introductionmentioning
confidence: 98%
“…Thus, an overall activation energy cannot be determined with high accuracy as, for example, surface interactions cannot be fully considered as well. For the rate‐limiting steps of the selective hydrogenation of acetylene on ZnPd, AlPd, GaPd and GaPd 2 surfaces activation barriers of 56, 71, approximately 70–106 and approximately 80 kJ mol −1[38] have been calculated, which are significantly higher than experimental values. Calculations for monometallic Pd surfaces (32–60 kJ mol −1 ) are in agreement with experimental values, owing also to the high variance of measured and calculated activation energies.…”
Section: Resultsmentioning
confidence: 99%